Influence of BG-11 culture media on growth of Cyanobacteria, Oscillatoria Species - Yadav, A.; Dubey, K.; Parveen, S.; Rout, S.; Singh, D. (IJRDO-Journal of Applied Science, 2016)
Oscillatoria species is a Cyanobacteria that is important because it can conduct photosyntheticactivities. it has a long un branching filamentous morphology and is green colour due to thechlorophyll content which is the unique features that set it apart from other. In this investigationit was cultured on BG-11 media and influences the growth after 1st week, parameters recordedi.e., fresh weight (2.04g) and dry weight (0.08 g) at room temperature. On 4th week fresh weight(at room temperature) recorded (1.18 g) and dry weight (0.1g). Culturing of Cyanobactria,Oscillatoria species is the part of biotechnolgy but they play a very important role in all the fieldof environmental science and biology.